(untitled) (GYMNASIUM, 2010)
Taking into account the fact that motor skills are "endogenous motor premises that allow the formation of motor abilities" the dynamics of the instructive-educational process is mainly about developing them for increasing the fitness of the body. The results in the control drills emphasize a progress made in the seven assessment tests. The progress regarding the arithmetical means was in the 50 m run, of 0.45 seconds for the 9th grade, 0.32 seconds for the10th grade; in the endurance run, of 15.67 seconds for the 9th grade, 13.40 seconds for the 10th grade; in the long jump, of 13 cm for the 9th grade, 6 cm for the 10th grade; in the standing spring, of 0.85 cm for the 9th grade, 0.88 cm for the 10th grade; in the runup spring, of 1.39 cm for the 9th grade, 0.83 cm for the 10th grade; throwing the medicinal ball forward - 0.55 m for the 9th grade, 0.44 for the 10th grade; throwing the medicinal ball backward - 0.74 m for the 9th grade, 0.18 for the 10th grade. In each grade there was an obvious progress, as a result of the training centered on the development of psycho-motor skills.